An Examination of an Interviewer-Respondent Matching Protocol in a Longitudinal CATI Study. (12th February 2019) - West, Brady T; Elliott, Michael R; Mneimneh, Zeina; Wagner, James; Peytchev, Andy; Trappmann, Mark
Abstract: This article presents results from an experimental study in Germany designed to test the effectiveness of a novel protocol for matching participants in a national panel survey with interviewers employing computer-assisted telephone interviewing (CATI) on selected sociodemographic features, including sex, age, and education. We specifically focus on the ability of the protocol to engender close matches between respondents and interviewers in terms of these features, using both theory and empirical evidence to suggest that this type of matching will improve cooperation rates in surveys employing CATI. We also focus on indicators of "success" at first contact (defined as a successful interview or establishment of an appointment for an interview) as a function of whether the matching protocol was in use on a given day and whether specific types of matches generated higher rates of success overall. We find strong evidence of the protocol effectively establishing close matches, and we also observe that matches based on education proved especially effective for rates of "success" in a panel survey that focused primarily on labor market topics. We conclude with thoughts on practical implementation of this approach in other settings and suggested directions for future work in this area.